Learning Styles among students of three different Universities in Dentistry in Brazil: Transversal study (Research, Society and Development, 2022)
Learning styles indicate the ways and conditions in which students understand, retain, and memorize knowledge in a productive and responsive manner. One of the most widely used tools to assess learning styles is the VARK (Visual, Aural, Read/write, and Kinesthetic) questionnaire. To identify the learning styles of students enrolled in three different dentistry programs in Brazil by applying the VARK questionnaire. This cross-sectional study involved a sample of 340 undergraduate students enrolled in dentistry programs at the following institutions: Federal University of Minas Gerais (n=172), Pontifical Catholic University of Minas Gerais (n=100), and Pontifical Catholic University of Paraná (n=68). An online questionnaire was administered to the students via “Qualtrics CM 2020”, between May 2020 and September 2020. It comprised questions about the student`s demographic, socioeconomic, and academic characteristics. Their learning style was assessed by the VARK questionnaire. The chi-squared test and Z-test were used to analyze the relationship between learning styles, considering p